Embolization of congenital portosystemic shunt presenting after pediatric liver transplantation: Case report and literature review. (14th May 2020) - Rohringer, Taryn J.; Ng, Vicky L.; Amaral, Joao G.; Parra, Dimitri A.
Abstract: This case report describes a 13‐year 10‐month‐old girl who underwent a deceased‐donor split LT for primary diagnosis of biliary atresia at the age of 12 months, who presented with a lower GI bleed. Ultrasound and CT revealed a venous vascular anomaly involving the cecum and ascending colon, with communication of the SMV and pelvic veins consistent with a CEPS. Associated varices were noted in the pelvis along the uterus and urinary bladder. These findings were confirmed by trans‐hepatic porto‐venography, which was diagnostic and therapeutic as a successful embolization of the CEPS was performed using micro‐coils. There were no complications following the procedure and no further GI bleeding occurred, illustrating the efficacy of this treatment option for CEPS. We discuss the literature regarding the presenting complaint of GI bleeding post–LT, CEPS as a rare cause of GI bleeding and its association with PV, and the classification and treatment of CEPS.